How Effective is the Green Financing Framework for Renewable Energy? A Case Study of PT Pertamina Geothermal Energy in Indonesia - Aransyah, Muhammad Fikry (International Journal of Energy Economics and Policy, 2023)
This paper assesses the green financing framework for renewable energy in Indonesia, with a focus on PT Pertamina Geothermal Energy (PGE) as a case study. PGE is a state-owned company and a significant producer of geothermal energy in Indonesia. The paper evaluates the strengths and weaknesses of PGE’s green financing framework, including its reliance on government policy and regulation, the speed and efficiency of disbursement of funds, and the quality of project selection. The paper also examines PGE’s intention to engage external auditors to verify its internal tracking method and allocation of funds, which aligns with global best practices in green financing. The involvement of external reviewers adds an extra layer of oversight and credibility to the process. Overall, the paper concludes that PGE has a strong framework in place for managing green financing, with several projects in various stages of implementation. However, there is room for improvement in terms of project selection criteria and impact reporting accuracy and reliability. In summary, this paper provides valuable insights into the green financing framework for renewable energy in Indonesia, with a specific focus on PGE as a case study.